2021
DOI: 10.15414/afz.2021.24.01.25-34
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of the adoption of agroforestry technology on food production and poverty reduction among farming households in Oyo State, Nigeria

Abstract: Licensed under a Creative Commons Attribution 4.0 International License This study determines the impact of agroforestry practices on food production, income generation and poverty reduction among farming households in Oyo State, Nigeria. A multi-stage sampling technique was used to select the respondents. Both descriptive statistics such as frequencies and percentages as well as inferential statistics such as Propensity Score Matching (PSM) and Foster Greer Thorbecke (FGT) analysis were used in the study. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(9 reference statements)
1
3
0
Order By: Relevance
“…Food expenditure and total crop output are significant with a negative relationship with the total income of the contact farmers at 5 and 1%, respectively. These claims are in consonance with the findings of Idumah et al (2021) and Ginting et al (2020).…”
Section: Income Modelsupporting
confidence: 91%
“…Food expenditure and total crop output are significant with a negative relationship with the total income of the contact farmers at 5 and 1%, respectively. These claims are in consonance with the findings of Idumah et al (2021) and Ginting et al (2020).…”
Section: Income Modelsupporting
confidence: 91%
“…The results of this study are in accord with the work of [28], who argued that learning increases farmers' perceptions of and preferences for innovation adoption. Yet, studies conducted by [35,36] showed that the percentage of agroforestry adopters is lower than that of non-adopters. Several constraints can hinder adoption [35], including the lack of willingness to plant trees and wait for two years to achieve the benefits of this innovative technology.…”
Section: Analysis Of the Proportion Of Adopters And Non-adopters Of A...mentioning
confidence: 99%
“…The last group can be used as caterpillar host species or for apiforestry (beekeeping in a treed environment) and aquaforestry (fish ponds or rice paddies dotted with trees). For [36], the constraints mitigating the adoption of agroforestry technologies by farmers include, among others, insufficient land for tree planting, the illegal felling of trees, the long developmental period of trees, the lack of technical assistance, the lack of planting materials, the lack of knowledge and skills, as well as competition between trees and arable crops on farmland.…”
Section: Analysis Of the Proportion Of Adopters And Non-adopters Of A...mentioning
confidence: 99%
“…The agroforestry was introduced to protect agricultural lands from soil erosion and degradation (Idumah et al, 2021), while ensuring yields of crops for sustainable food system. It is a technique to managing agro-ecosystems for improved and sustained productivity, increased profits and food security while preserving and enhancing the resource base and the environment (FAO, 2014;Vaiknoras, 2015;Duffy et al, 2021).…”
Section: Introductionmentioning
confidence: 99%